Pengaruh Trust Dan Perceived Ease Of Use Terhadap Intention Kaum Milenial Dalam Menggunakan Aplikasi E-Commerce Shopee Yang Dimediasi Oleh Perceived Of Usefulness - Haning, Melaningtyas Tesalonika (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the influence of Trust, Perceived ease of use on Intention with Perceived of Usefulness as Mediation for millennials in using application-based transportation. Many millennials currently use the Shopee e-commerce application. In Indonesia alone, there are various kinds of well-known e-commerce in this community such as Shopee, Pedia Shop, Buka, Lazada and others. Sometimes we get confused between these e-commerce. That's why in this study, researchers want to know what factors influence the millennial generation. Researchers narrow down three variables, trust, perceived ease of use, and perceived usefulness. This research is using quantitative type of reasearch and choosing 100 people (male & female, 18-26 years old, and uses Shopee e-commerce) assubjects research. Researchers used the SPSS application to test the results of the study. The results showed that the most influential factor in influencing the intention to use application-based transportation was perceived usefulness, followed by perceived ease of use, and the last one that had the least effect was trust. Keywords : e-commerce, perceived usefulness, sense of ease of use, and trust